2001
DOI: 10.1007/s004080000058
|View full text |Cite
|
Sign up to set email alerts
|

Different Expression of Endothelin in the Bronchoalveolar Lavage in Patients with Pulmonary Diseases

Abstract: Endothelin (ET) is a broncho- and vasoconstrictive cytokine, but it also possesses proinflammatory and mitogenic activity. It is suggested to be involved in the pathogenesis of fibrotic lung diseases. We analyzed the concentration of ET 1 in the bronchoalveolar lavage (BAL) fluid in 95 patients with different lung diseases, among them 41 patients with interstitial lung diseases (13 fibrosing alveolitis in systemic sclerosis (FASS), 9 idiopathic pulmonary fibrosis (IFP), 8 sarcoidosis (S), 6 occupational lung d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 0 publications
1
43
1
1
Order By: Relevance
“…The observed concentrations of active ET-1 are consistent with those reported in scleroderma fibroblasts exposed to TGF-b (7,15). Similar concentrations of ET-1 were found in the epithelial lining fluid of patients with ARDS and bronchoalveolar lavage fluid of patients with interstitial lung disease (44)(45)(46). Although the concentration of ET-1 secreted by mesenchymal cells stimulated with TGF-b1 in vitro approximates these levels reported in vivo, the effective concentration of ET-1 within fibrotic tissue remains unclear, and may be markedly higher within the pericellular microenvironment.…”
Section: Discussionsupporting
confidence: 79%
“…The observed concentrations of active ET-1 are consistent with those reported in scleroderma fibroblasts exposed to TGF-b (7,15). Similar concentrations of ET-1 were found in the epithelial lining fluid of patients with ARDS and bronchoalveolar lavage fluid of patients with interstitial lung disease (44)(45)(46). Although the concentration of ET-1 secreted by mesenchymal cells stimulated with TGF-b1 in vitro approximates these levels reported in vivo, the effective concentration of ET-1 within fibrotic tissue remains unclear, and may be markedly higher within the pericellular microenvironment.…”
Section: Discussionsupporting
confidence: 79%
“…An imbalance in vasoconstrictor and vasodilatory mediators among patients with sarcoidosis and PH has also been shown. Increased levels of the potent vasoconstrictor endothelin-1 have been described in BAL fluid 26 and serum 27 in patients with sarcoidosisrelated PH. Another study 16 reported evidence of increased pulmonary production of thromboxane A 2 during a period of vasodilator-induced increase in pulmonary blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…A second paradigm is that there are pat- terns of chemokine and/or cytokine expression in patient BAL which appear to correlate with progression of the fibrotic process. The group of profibrotic mediators shown in Table 2 are elevated in the BAL and tissues of several of the disorders listed in Table 1, though the majority of studies have been done with patients thought to have IPF (18)(19)(20)(21)(22)(23)(24). Because individual chemokines, cytokines, and leukotrienes act at multiple points and regulate each others' expression levels, determining the importance of any single mediator among these patients remains a challenge.…”
Section: Historical Perspectives and Emergence Of Current Conceptsmentioning
confidence: 99%